2016
DOI: 10.1007/s00784-015-1707-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride toothpaste supplemented with sodium hexametaphosphate reduces enamel demineralization in vitro

Abstract: This dentifrice could potentially be indicated to patients at high risk of caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
(45 reference statements)
3
31
0
Order By: Relevance
“…When used at high concentrations, SMTP has the ability to supersaturate the enamel surface and further sequester Ca 2+ from hydroxyapatite due to its strong ability to complex metal ions, resulting in mineral loss [da Camara et al, 2016]. Although this evidence was reported for enamel, a similar mechanism is expected for dentin.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…When used at high concentrations, SMTP has the ability to supersaturate the enamel surface and further sequester Ca 2+ from hydroxyapatite due to its strong ability to complex metal ions, resulting in mineral loss [da Camara et al, 2016]. Although this evidence was reported for enamel, a similar mechanism is expected for dentin.…”
Section: Discussionmentioning
confidence: 88%
“…5c). It can be speculated that the addition of high concentrations of STPM to the medium may have supersaturated the dentin tissue, leading to sequestration of Ca 2+ from the dentin [Anbar et al, 1979;Changgen and Yongxin, 1983;da Camara et al, 2016]. Supposedly, the concentrations of 3.5 and 5% were able to decrease the Ca/P ratio of these groups, since this is the main reason of calcium loss, which impaired remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…One way to reduce the potential risk of fluorosis while maintaining the anticaries efficacy of conventional dentifrices is to partly replace fluoride with polyphosphate salts like sodium trimetaphosphate (STMP), calcium glycerophosphate, or hexametaphosphate [da Camara et al, 2016;Takeshita et al, 2016;Zaze et al, 2014]. Among the polyphosphates, STMP is seen to be the most effective anticaries agent with an ability to not only inhibit demineralization, but also to enhance remineralization [Freire et al, 2016;Takeshita et al, 2011].…”
Section: Fluoride Boostersmentioning
confidence: 99%
“…As HMP associated to 1,100 ppm F did not enhance enamel F uptake [Dalpasquale et al, 2017;da Camara et al, 2015;da Camara et al, 2016], the superior results with nano-sized HMP is probably due to the higher reactivity of these particles [Dalpasquale et al, 2017]. Given that the anticaries effect of fluoride toothpastes (i.e., without HMP/HMPnano) is usually related to the ability to increase enamel fluoride concentrations, it can be concluded that the mechanism of action of HMP/ HMPnano containing fluoride toothpastes is somehow different from products containing fluoride only.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the development of new toothpaste formulations to enhance anticaries effects has been investigated; formulations include the addition of inorganic phosphate salts Takeshita et al, 2015;Danelon et al, 2017]. Among these, micrometric sodium hexametaphosphate (HMP) has a strong affinity to the enamel surface because of multiple binding sites, resulting in a reduced mineral loss when associated with fluoride as demonstrated by da Camara et al [2014;2016].…”
Section: Introductionmentioning
confidence: 99%